Perancangan Aplikasi E-Commerce Berbasis Website Studi Kasus PT Grahanindo Mecanitron - Louis, Laurencius; Tjiong, Edwin Lesmana (UNIVERSITAS KALBIS, 2025)
The purpose of this research is to create an e-commerce for selling pump products for PT. Grahanindo Mecanitron. The current working system, which has not yet adopted modern technology, can cause disruptions in the buying and selling process. Therefore, this application is created to facilitate the company in processing pump sales. The method used to build this application is the Scrum method with Unified Modeling Language (UML) modeling and MERN Stack with Chakra UI styling for application development. The application is tested using black box testing. The result of this research is a web-based e-commerce application.